Reconfiguring the natures of childhood - Taylor, Affrica (Contesting early childhood., 2013)
In this fascinating new book, Affrica Taylor encourages an exciting paradigmatic shift in the ways in which childhood and nature are conceived and pedagogically deployed, and invites readers to critically reassess the naturalist childhood discourses that are rife within popular culture and early years education. Through adopting a common worlds framework, Reconfiguring the Natures of Childhood generates a number of complex and inclusive ways of seeing and representing the early years. It recasts childhood as:messy and implicated rather than pure and innoce.